Design and simulation of core-ring magnet configurations for maximising energy transduction in linear actuators and micro-energy generators - Gatti, R.; Howard, Ian; Lumentut, M. (2016)
© 2016 IEEE.The Linear energy harvesters and actuators employ electromagnetic induction principles to generate electrical energy or motion. The most common configurations for such actuators are cylindrical ring magnets with coils inside or cylindrical magnets with coils surrounding the magnets. A series of numerical FEA analyses were performed to design and simulate different core-ring magnet configurations to identify the best possible combination for maximum energy transduction. It was observed that the tapered ring magnet - tapered core configuration had the highest magnetic spatial variation and thus suitable for maximum energy transduction. This study can be applied to design linear actuators, linear electromagnetic energy harvesters and from microscale to macroscale applications.